Pengaruh Artificial Intelligence terhadap Kecepatan dan Akurasi Sistem Informasi Akuntansi - Judijanto, Loso; AR, Mulyadi (Jurnal Akuntansi Dan Keuangan West Science, 2025)
This study examines the impact of artificial intelligence (AI) on the speed and accuracy of accounting information systems (AIS) in Indonesia, using a quantitative research approach. Data were collected from 38 respondents representing businesses that have implemented AI in their accounting processes. A structured questionnaire employing a 5-point Likert scale was used to measure perceptions of AI's effects on AIS performance. The data were analyzed using SPSS version 25, employing descriptive statistics, correlation, and regression analyses. The results indicate that AI integration significantly improves both the speed and accuracy of AIS, with accuracy showing a slightly stronger impact. These findings highlight AI's potential to enhance decision-making, operational efficiency, and financial reporting quality. This study contributes valuable insights for practitioners and policymakers aiming to optimize accounting practices through AI adoption.